2018
DOI: 10.21037/qims.2017.10.10
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone microstructure is impaired in the proximal femur of human immunodeficiency virus-infected men with normal bone mineral density

Abstract: Background: There is evidence that human immunodeficiency virus (HIV) infection and antiretroviral therapy (ART) are independent risk factors for osteoporosis and fracture which is not solely explained by changes in bone mineral density. Thus, we hypothesized that the assessment of trabecular microstructure might play an important role for bone quality in this population and might explain the increased fracture risk. In this study, we have assessed bone microstructure in the proximal femur using high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…In vivo microstructural analysis of high-resolution MRI of the proximal femur has been clinically applied to postmenopausal women with osteoporosis, 47,71 long-term glucocorticoid users, 48 as well as human immunodeficiency virus-infected (HIV) men. 45 Patients with fractures had lower elastic modulus than the control group in all proximal femur regions but no differences in T-scores. 47 Another study investigated 60 postmenopausal women (30 with and 30 without fragility fractures) who did not have osteoporotic BMD in the proximal femur; however, the fracture group was found to have significantly impaired bone microstructure.…”
Section: Application and Main Findingsmentioning
confidence: 75%
See 3 more Smart Citations
“…In vivo microstructural analysis of high-resolution MRI of the proximal femur has been clinically applied to postmenopausal women with osteoporosis, 47,71 long-term glucocorticoid users, 48 as well as human immunodeficiency virus-infected (HIV) men. 45 Patients with fractures had lower elastic modulus than the control group in all proximal femur regions but no differences in T-scores. 47 Another study investigated 60 postmenopausal women (30 with and 30 without fragility fractures) who did not have osteoporotic BMD in the proximal femur; however, the fracture group was found to have significantly impaired bone microstructure.…”
Section: Application and Main Findingsmentioning
confidence: 75%
“…71 One study in eight HIV-infected men found significantly lower bone quality compared to healthy controls, but BMD did not show significant differences between HIV-infected patients and healthy controls. 45 These findings suggest that assessment of trabecular bone microarchitecture might play an important role in the context of bone quality in addition to BMD measurements.…”
Section: Application and Main Findingsmentioning
confidence: 92%
See 2 more Smart Citations
“…A 72% diagnostic accuracy was computed [ 94 ]. Furthermore, a strong negative correlation was found between the pelvic bone marrow adipose tissue (BMAT) calculated in 56 healthy women using MRI and the corresponding DXA-based BMD (r = −0.646, p < 0.001) [ 95 ]. The negative correlation indicates that patients with decreased bone mineral density are characterized by an increased fat content in bone marrow [ 95 , 96 , 97 ].…”
Section: Mri Based Approachmentioning
confidence: 99%